A novel mutation of thyroid hormone receptor beta (I431V) impairs corepressor release, and induces thyroid hormone resistance syndrome - Azevedo, Monalisa Ferreira (2008)
ABSTRACT: Resistance to thyroid hormone (RTH) is a rare disorder characterized by variable tissue hyporesponsiveness to thyroid hormone, usually caused by mutations in the thyroid hormone receptor beta (TRβ). We describe a large Brazilian family harboring a novel mutation affecting TRβ gene and inducing RTH. A 14-year-old girl was found to have elevated free T4 and free T3 plasma concentrations in coexistence with unsuppressed TSH and a questionable goiter. The diagnosis of RTH was verifi ed by identifi cation of a novel mutation (I431V) in the TRβ gene. Sixteen asymptomatic relatives of the proposita are also affected by the mutation. Functional studies showed that I431V mutation exerts dominant-negative effect on wild type TRβ, mainly by impairment of ligand-dependent release of corepressor SMRT. The presence of this mutation reduces potency, but does not affect effi cacy of thyroid hormone action, in accordance with the clinical picture of eumetabolism of the affected individuals. _______________________________________________________________________________ RESUMO